2006
DOI: 10.1111/j.0021-9029.2006.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Causal Attributions, Perceived Control, and Psychological Adjustment: A Study of Chronic Fatigue Syndrome1

Abstract: Causal attributions control, beliefs, and helpful and unhelpful support attempts were examined among people experiencing chronic fatigue syndrome (CFS) and their close others. Results revealed that 84% of respondents with CFS believed that their illness was due, at least in part, to physical or external causes, whereas 47% mentioned internal/psychological causes. Reports of internal causal attributions for CFS were positively correlated with indicators of poor psychological adjustment among those with CFS. Hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…In line with study hypotheses, significant other negative responses were associated with increases in patient‐reported symptom severity and distress at the same momentary assessment. The relationship between negative significant other responses and increased patient depression has been documented cross‐sectionally (Romano et al ., ; White et al ., ) and patient depression has also been identified as predictive of poorer patient illness and treatment outcomes (Bentall et al ., ; Tamres et al ., ). A recent review of the existing evidence suggested that significant other negative responses may be important for patient illness outcomes by increasing levels of patient depression (Band et al ., ) supported by longitudinal evidence demonstrating the mediational role of increased patient depression between significant other criticism and fatigue severity (Band et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with study hypotheses, significant other negative responses were associated with increases in patient‐reported symptom severity and distress at the same momentary assessment. The relationship between negative significant other responses and increased patient depression has been documented cross‐sectionally (Romano et al ., ; White et al ., ) and patient depression has also been identified as predictive of poorer patient illness and treatment outcomes (Bentall et al ., ; Tamres et al ., ). A recent review of the existing evidence suggested that significant other negative responses may be important for patient illness outcomes by increasing levels of patient depression (Band et al ., ) supported by longitudinal evidence demonstrating the mediational role of increased patient depression between significant other criticism and fatigue severity (Band et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It means that for some people illness is deserved. Blaming patients for becoming ill has negative effects on their well-being and on the care they receive (Barrowclough & Hooley, 2003;Ladany et al, 1998;Lobchuk, McClement, McPherson, & Cheang, 2008;Salmon & Hall, 2003;White, Lehman, Hemphill, Mandel, & Lehman, 2006). Decision makers allocating medical resources may also be biased against patient groups they hold responsible for their illness (Furnham & Proctor, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The most common attribution was to a virus or post-viral infection (Powell et al, 1990;Wessely & Powell, 1989;White, Lehman, Hemphill, Mandel, Lehman, 2006;Sharpe et al, 1992;Vercoulen et al, 1994;Edwards et al, 2001;Heijmans, 1998;Evengard et al, 2003). However, a point worth considering is that several of these studies show a large minority of CFS participants making other types of attributions.…”
Section: Psychoanalytic Psychotherapy 147mentioning
confidence: 99%
“…Butler et al (2001) found 28% of individuals made normalising attributions. White et al (2006) reported that 47% in part made a psychological attribution. found that 31% reported emotional stress as contributing to their fatigue and Edwards et al (2001) and Heijmans (1998) reported that 24% acknowledged that their symptoms could be psychological.…”
Section: Psychoanalytic Psychotherapy 147mentioning
confidence: 99%